10-6x-3=2(-3-3)

Simple and best practice solution for 10-6x-3=2(-3-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-6x-3=2(-3-3) equation:


Simplifying
10 + -6x + -3 = 2(-3 + -3)

Reorder the terms:
10 + -3 + -6x = 2(-3 + -3)

Combine like terms: 10 + -3 = 7
7 + -6x = 2(-3 + -3)

Combine like terms: -3 + -3 = -6
7 + -6x = 2(-6)

Multiply 2 * -6
7 + -6x = -12

Solving
7 + -6x = -12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -6x = -12 + -7

Combine like terms: 7 + -7 = 0
0 + -6x = -12 + -7
-6x = -12 + -7

Combine like terms: -12 + -7 = -19
-6x = -19

Divide each side by '-6'.
x = 3.166666667

Simplifying
x = 3.166666667

See similar equations:

| 5.2+1.2n=1.84 | | 10u=54+u | | 2(-2)-3+(-2)+1= | | 2x-20=3x+6 | | 0.5x+x=169 | | -3/7(-40-2) | | Cos(x)=0.018 | | 18=-3/7(x-2) | | 3(2x-5y)=z | | -5(8r+3)=-5(7r-5) | | 1(8+x)=7 | | 6c+11=2c+51 | | .5(x+8)=-5 | | 6-22(x+6)=2 | | 4x-7(-7-9)=42 | | 6(3+3m)=3(3m+3) | | x^2-8x=-102 | | 6b+9=5b+17 | | 2.5(6x-4)=10+(1.5+0.5x) | | -7+13=4+n | | (0-6)(2x+1)=0 | | 10a-3=6a+33 | | 16=2(x-1)-6 | | 5a^2-9ab+8a= | | .30x+.50= | | -4.5=5x-x-x | | .30x+.5= | | -10(s+4)=-62 | | 2x+2=11x-70 | | 32+2+2=3.2 | | 2(f-1)=-4 | | x+2-3x=-8 |

Equations solver categories